Factors Inhibiting the Mentally Challenged in the Acquisition of Skills in Ugenya District, Siaya County, Kenya - SIKA, JAMES OCHIENG (Advances in Social Sciences Research Journal, 2015)
Abstract The study focus was on factors inhibiting the mentally challenged in the acquisition of skills. Objectives were to establish the challenges facing mentally handicapped learners in acquisition of learning skills; to establish the effect of parents and community support and involvement on the acquisition of learning skills; to determine the effect of the role of teachers and teaching methods used on the acquisition of learning skills; and to find out the effect of learners characteristics on the acquisition of learning skills among mentally handicapped learners. Descriptive survey design and purposive sampling techniques were used to sample the respondents. A total of 76 respondents responded to the research instruments. Among the major findings, the study established that the major challenges facing the acquisition of leaning among the mentally handicapped included: students’ involvement in interruptive behaviours which interferes with cognitive functioning and inability to cope with frustrations. The role of teachers and teaching methods was not a hindrance to the acquisition of learning skills among the mentally challenged students. The study recommended that awareness should be created through dissemination of information on mental handicap learners. The study suggests a comparative study on the process of acquisition of learning skills be done among normal and mentally challenged learners.